Aspek Wakaf Tunai dalam Investasi Abadi Umat - Idrus, Ali; Amirsyah, Amirsyah; Matondang, M. Reza Prima; Nuryadin, Deni; Fahriah , Putri Haezah; Nurfauzi , Utari (STAINI Press, 2024)
Nowadays, the existence of waqf is no longer always in the form of land intended for educational institutions, places of worship, mass graves or for momentary needs, but the benefits of waqf are not yet known by many ordinary people. For this reason, waqf needs to be managed productively in order to improve the welfare and economy of the people, one of the productive waqf is cash waqf. Explicitly, cash waqf is not explained in the nash al-Qur'an and Hadith. This is what makes cash waqf has different opinions. The majority of scholars have said that cash waqf can be practiced based on the consideration of ijtihad and istinbath methods. Conceptually, permanence is also not an absolute thing because there is an opinion that accommodates temporariness. This opinion is accommodated in cash waqf. The concept of cash waqf is a concept to raise endowment funds that can bring benefits to the ummah